Предмет: Математика,
автор: vyvvyv2017
(2y-6)*(6-4y)=0 помагите пожалуста
Ответы
Автор ответа:
0
(2y - 6)*(6 - 4y) = 0
-36 - 8y²+ 36y = 0
D = (36)² - 4*(-8)*(-36) = 144
y=(-b+-√D)/2a
y₁=3/2
y₂=3
-36 - 8y²+ 36y = 0
D = (36)² - 4*(-8)*(-36) = 144
y=(-b+-√D)/2a
y₁=3/2
y₂=3
Автор ответа:
0
я в 6 классе
Похожие вопросы
Предмет: География,
автор: nastyahka78
Предмет: Биология,
автор: juriakimu887
Предмет: Химия,
автор: panasinavarvara
Предмет: Математика,
автор: kauts72
Предмет: Алгебра,
автор: superleron